Harnessing Stem Cells for Kidney Regeneration : Progresses and Challenges in Clinical Translation - Ni Luh Wisma Eka Yanti; Anak Agung Dita Hendrawan; Maqfirah Muryanifa (International Journal of Health and Social Behavior, 2025)
The prevalence of chronic kidney disease is increasing worldwide and is considered a burden for health care systems and patients. However, there are only a few treatment options, and in most cases, the end-stage of the disease requires renal replacement. Stem cell-based therapy has gained popularity as a cutting-edge strategy in the field of regenerative nephrology. Numerous clinical studies on evaluating stem cells safety and tolerability have been carried out, leading to clinical translation of stem cells for kidney regeneration. This study will focues on progresses of recent clinical trials on stem cell therapy for various kidney diseases, while also highlighting key challenges in clinical translation and future directions in the field of regenerative nephrology.